(3TQM GdebGeGJ GdMQjQjs - (3CHi YHO Gddg MLI GdOjf eMeO Hf YHO Gddg CHi eMeO Hf eMeO Hf XaQ GdUbdj Gdecjs; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdYde CQaY fSH hCfaY ecJSH hEf JCKjQ GdYdeGA ai GdMcGe cJCKjQ GdCdHGH ai GdCLSGe s
(3BNQgG (B:s
(3hJdGTi GdJYGXe hGdESJHOGO CSJhba Gddg dChd JhLg EdjfG bhGg agh MSHi hfYe Gdhcjd s
(3GdTQM GdUZjQs
(3GhdgG JYQja HEHf XaQ GdTGQMs
(3HGdeYgO fSNJGf CNQjGJ GfXQ ai GdbSe GdKGfi GdQbejf (B1196(3, (B1197 (3COHs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs